Pelatihan Activité Ludique untuk Guru Bahasa Prancis SMA Di DKI Jakarta - Wahyu Tri Widyastuti; Ekowati, Sri Harini; Purbarini, Asti; Ismayani, Ria (Universitas Nusantara PGRI Kediri, 2021)
The Law of the Republic of Indonesia No. 14 of 2005 concerning Teachers and Lecturers states that one of the duties of teachers and lecturers as professional education personnel is to plan, carry out a quality learning process, assess and evaluate learning outcomes. The expected learning outcomes are able to deliver students to have communication skills, collaboration skills, critical thinking skills and problem solving skills, creativity and innovation skills. . In response to this, teachers and lecturers must improve and develop academic qualifications and competencies on an ongoing basis according to the times. To realize this, teachers and lecturers can take part in training. The P2M team of UNJ's French Language Education Study Program has organized Activités Ludiques (language games) training, namely training to teach French through innovative language games, which can deliver students to communicate, think critically, innovatively, creatively in accordance with the demands of this century. The training lasted for 20 hours, the participants consisted of French teachers at SMK and SMA in Jakarta. During the training they received material in the form of various language game platforms namely Kahoot, Quizizz, Learning Apps, Quizlet, Educative Logiciel, Jeu de l'oie, Qu'est-ce qu'il manque. With this training, the P2M Team of the French Language Education Study Program, UNJ hopes that the training participants, consisting of French vocational high school and high school teachers in Jakarta, can improve their competence and professionalism.